Kirsti Aasen: Alle mine kilder - Nielsen, Helge Baden (Grundtvig-studier, 1986)
Kirsti Aasen: A ll M y Springs. Gyldendal Norsk Forlag, Oslo 1986.Reviewed by Helge Baden Nielsen. The title of the book are the first words of one of Grundtvig’s hymns. The reviewer sees this essay collection by a Norwegian woman minister first and foremost as an expression of the new interest in Grundtvig in Norway, as was proved by the establishment in 1983 of a special Norwegian branch of the Grundtvig Society. According to Kirsti Aasen this takes its origin in the liberation, under Grundtvig’s inspiration, from the pietistic view of Christianity in Norway. In her own case she discovered that Christianity could easily be combined with love of the Norwegian countryside and the life of the people. The author was born in .sterdalen, studied theology at Oslo University, and is now rector of a parish in Oslo.